2015
DOI: 10.1097/jto.0000000000000519
|View full text |Cite
|
Sign up to set email alerts
|

Patients Selected for Definitive Concurrent Chemoradiation at High-volume Facilities Achieve Improved Survival in Stage III Non–Small-Cell Lung Cancer

Abstract: Our findings suggest that treatment at HVF is associated with improved overall survival among stage III NSCLC patients receiving definitive CCRT, independent of academic affiliation. Further research is needed to determine whether or not efforts supporting centralization of radiotherapy at HVF will improve population-based survival, toxicities, and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
73
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 49 publications
7
73
1
Order By: Relevance
“…We believe this case volume effect is likely true for other disease sites besides prostate cancer, as Wang et al (12) also recently reported improved survival for patients treated at high-volume facilities in the setting of concurrent chemoradiation for stage III non-small cell lung cancer. There are multiple potential reasons underlying this effect.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We believe this case volume effect is likely true for other disease sites besides prostate cancer, as Wang et al (12) also recently reported improved survival for patients treated at high-volume facilities in the setting of concurrent chemoradiation for stage III non-small cell lung cancer. There are multiple potential reasons underlying this effect.…”
Section: Discussionmentioning
confidence: 85%
“…This association was attributed to the hospital and surgeon's experience which yielded improved rates of achieving negative margins (6)(7)(8) and higher rates of dissecting involved lymph nodes (6,9,10). However, there is limited data about whether this volume effect exists in radiation-treated cancer patients (11), and whether treatment at a radiation facility that treats a high case volume of cancer patients is associated with improved survival (12). To explore this possibility, we conducted a nationwide cancer database analysis to specifically compare the overall survival of radiation-treated high-risk prostate cancer in high versus low radiation case volume (RCV) facilities.…”
Section: Introductionmentioning
confidence: 86%
“…An increasing amount of data supports the hypothesis that radiation therapy by high-volume providers is associated with improved outcomes in HNC [13,14] and multiple non-HNC malignancies like lung, cervical, and prostate cancers [15][16][17][18]. In HNC, two recent large national database analyses have noted disparities in access to high-volume providers, which may serve as another proxy for access to high-quality cancer care.…”
Section: Evidence Of Radiation Therapy Delivery Disparities In Hncmentioning
confidence: 81%
“…13 Indeed, the findings by Chen et al 4 add to a growing body of evidence in other cancer types relating provider experience to improved oncological outcomes in patients treated with definitive radiation, with recent reports indicating similar relationships in patients undergoing definitive radiation for cervical cancer and definitive chemoradiation for stage III non-small-cell lung cancer. 5, 6 …”
mentioning
confidence: 99%